PELATIHAN ANALISIS REGRESI DENGAN SOFTWARE STATISTIK UNTUK MENINGKATKAN KUALITAS PENELITIAN DOSEN POLITEKNIK KESEHATAN JAMBI - gusmi kholijah; Niken Rarasati; Corry Sormin; Gusmanely Z; Jevi Perdana (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2023)
Lecturer is a profession that has the obligations of the Tridharma of Higher Education. Tridharma includes teaching, research and community service. Each tridharma element must be properly measured as the performance of a lecturer. Lecturer performance in research can be assessed from the quality of the output. The outputs of lecturer research activities are required to be published so that they can be known and become a public reference. Thus, published research results must be properly presented. Problems were found in analyzing the data by the lecturers of the Health Polytechnic of the Jambi Ministry of Health when carrying out the research. So far, data analysis has been limited to analysis of variance (ANOVA). The drawback in using analysis of variance alone in research is that errors will appear in drawing conclusions. Therefore, to overcome these problems, regression analysis training was held to improve the quality of lecturer research at the Jambi Ministry of Health Polytechnic as a form of dedication by lecturers from Jambi University. The activities carried out were in the form of workshops and practice of regression analysis for health cases using Minitab and SPSS software, besides that, interpretation of the results was also carried out. The community service activities carried out were carried out according to the plan, then this activity received a good response from the lecturers at the Jambi Health Polytechnic. This training activity also provides opportunities for communication and collaboration between lecturers from different fields and agencies. Keywords: Regression Analysis, Minitab, Community Service, SPSS